Early Prediction of Nonresponders to Treatment with Interferon Alpha-2B and Ribavirin in Patients with Chronic Hepatitis C - Louis WC Liu; George Tomlinson; Tony Mazzulli; Alison Murray; Jenny Heathcote (Canadian Journal of Gastroenterology)
BACKGROUND: Treatment of chronic hepatitis C virus (HCV) infection with interferon alpha-2b and ribavirin is costly in terms of side effects, medical resources and drug costs. Furthermore, less than 50% of patients overall have a sustained virological response (SVR).